Decent work - Ghai,Dharam (ed.) (New Delhi, 2007)
The volume is the output of an Institute Project for the Preparation of Pedag ogical Materials on Decent Work. The chapters included are based on studies prepared by eminent academics: Dharam Ghai, Bob Hepple, Martin Godfrey. Ashwani Saith and Sarosh Kuruvilla. They explain the dimensions of decent work with special reference to the four strategic objectives of the ILO. namely: Rights at Work, Employment, Social Protection and Social Dialogue. The volumen provides an introductory text to the concept, strategies and policies pertaining to decent work. They bring out the evolution and content of the concept and policies relating to key components of decent work and show their relevance and applicability to diverse institutional contexts and stages of development.
Keywords: Socialism